Sustained Weight Loss with Vagal Nerve Blockade but Not with Sham: 18-Month Results of the ReCharge Trial. (12th July 2015) - Shikora, Scott A.; Wolfe, Bruce M.; Apovian, Caroline M.; Anvari, Mehran; Sarwer, David B.; Gibbons, Robert D.; Ikramuddin, Sayeed; Miller, Christopher J.; Knudson, Mark B.; Tweden, Katherine S.; Sarr, Michael G.; Billington, Charles J.
Abstract : Background/Objectives . Vagal block therapy (vBloc) is effective for moderate to severe obesity at one year. Subjects/Methods . The ReCharge trial is a double-blind, randomized controlled clinical trial of 239 participants with body mass index (BMI) of 40 to 45 kg/m or 35 to 40 kg/m with one or more obesity-related conditions. Interventions were implantation of either vBloc or Sham devices and weight management counseling. Mixed models assessed percent excess weight loss (%EWL) and total weight loss (%TWL) in intent-to-treat analyses. At 18 months, 142 (88%) vBloc and 64 (83%) Sham patients remained enrolled in the study. Results . 18-month weight loss was 23% EWL (8.8% TWL) for vBloc and 10% EWL (3.8% TWL) for Sham (P < 0.0001 ). vBloc patients largely maintained 12-month weight loss of 26% EWL (9.7% TWL). Sham regained over 40% of the 17% EWL (6.4% TWL) by 18 months. Most weight regain preceded unblinding. Common adverse events of vBloc through 18 months were heartburn/dyspepsia and abdominal pain; 98% of events were reported as mild or moderate and 79% had resolved. Conclusions . Weight loss with vBloc was sustained through 18 months, while Sham regained weight between 12 and 18 months. vBloc is effective with a low rate of serious complications.